Transsulfuration in an adult with hepatic methionine adenosyltransferase deficiency. - W A Gahl; I Bernardini; J D Finkelstein; A Tangerman; J J Martin; H J Blom; K D Mullen; S H Mudd (The Journal of Clinical Investigation, 1988)
We investigated sulfur and methyl group metabolism in a 31-yr-old man with partial hepatic methionine adenosyltransferase (MAT) deficiency. The patient's cultured fibroblasts and erythrocytes had normal MAT activity. Hepatic S-adenosylmethionine (SAM) was slightly decreased. This clinically normal individual lives with a 20-30-fold elevation of plasma methionine (0.72 mM). He excretes in his urine methionine and L-methionine-d-sulfoxide (2.7 mmol/d), a mixed disulfide of methanethiol and a thiol bound to an unidentified group X, which we abbreviate CH3S-SX (2.1 mmol/d), and smaller quantities of 4-methylthio-2-oxobutyrate and 3-methylthiopropionate. His breath contains 17-fold normal concentrations of dimethylsulfide. He converts only 6-7 mmol/d of methionine sulfur to inorganic sulfate. This abnormally low rate is due not to a decreased flux through the primarily defective enzyme, MAT, since SAM is produced at an essentially normal rate of 18 mmol/d, but rather to a rate of homocysteine methylation which is abnormally high in the face of the very elevated methionine concentrations demonstrated in this patient. These findings support the view that SAM (which is marginally low in this patient) is an important regulator that helps to determine the partitioning of homocysteine between degradation via cystathionine and conservation by reformation of methionine. In addition, these studies demonstrate that the methionine transamination pathway operates in the presence of an elevated body load of that amino acid in human beings, but is not sufficient to maintain methionine levels in a normal range.